Executive Committee Minutes 2014-10-16 - Academic Senate:::::::::
Agenda amended and Approved. Minutes of 10/2 approved. Chair Report. Advance Practice Clinical Education certificate approved for Senate consent calendar. President Report. Vice Chair appointment for Spring 2015 approved. Vice Chair Report. Vice President of Administration and Finance Report. Vice President of Student Affairs Report. 2015 Faculty Retreat discussion. FSAC Request for feedback on an RTP revision. Revision to the Lecturers in Departmental Governance Policy referred back to FSAC. EPC Report. SAC Report. Associated Students Report. Ex Com Rep to SEC report. Senate Agenda approved. Good of the Order.